The surging role of Chromogranin A in cardiovascular homeostasis - Tota, Bruno; Angelone, Tommaso; Cerra, Maria C. (Frontiers in Chemistry, 2014)
Together with Chromogranin B and Secretogranins, Chromogranin A (CGA) is stored in secretory (chromaffin) granules of the diffuse neuroendocrine system and released with noradrenalin and adrenalin. Co-stored within the granule together with neuropeptideY, cardiac natriuretic peptide hormones, several prohormones and their proteolytic enzymes, CGA is a multifunctional protein and a major marker of the sympatho-adrenal neuroendocrine activity. Due to its partial processing to several biologically active peptides, CGA appears an important pro-hormone implicated in relevant modulatory actions on endocrine, cardiovascular, metabolic, and immune systems through both direct and indirect sympatho-adrenergic interactions. As a part of this scenario, we here illustrate the emerging role exerted by the full-length CGA and its three derived fragments, i.e. Vasostatin 1, catestatin and serpinin, in the control of circulatory homeostasis with particular emphasis on their cardio-vascular actions under both physiological and physio-pathological conditions. The Vasostatin 1- and catestatin-induced cardiodepressive influences are achieved through anti-beta-adrenergic-NO-cGMP signalling, while serpinin acts like beta1-adrenergic agonist through AD-cAMP-independent NO signalling. On the whole, these actions contribute to wide our knowledge regarding the sympatho-chromaffin control of the cardiovascular system and its highly integrated “whip-brake” networks.